Research on the function of GPX4 in tumor-targeted treatment based on its molecular structure and features - Geng, He; Ma, Lin; Wu, Lixin; Yao, Cuicui; Wang, Can; Gan, Xinyan; Li, Yiyi; Chen, Fang (Frontiers in Oncology, 2025)
GPX4 is the only antioxidant enzyme in mammals that can convert cholesterol and phospholipid hydroperoxide into phosphatidylol and cholesterol. Its peculiar molecular structure allows it to perform a variety of biological functions, including oxidative stress, ferroptosis regulation, brain development stimulation, and immune responses. In recent years, several studies have demonstrated that increased GPX4 expression is linked to tumor cell proliferation, growth, migration, and differentiation. Overexpression of GPX4 has been linked to chemoresistance and a poor prognosis in cancers including nasopharyngeal carcinoma, breast cancer, and lung cancer. GPX4 inhibitors have been demonstrated to be effective in the treatment of numerous drug-resistant malignancies. Some tumors, such as glioblastoma, do not react well to single-agent GPX4 inhibitors. Therefore, future research should focus on identifying cancers that are more responsive to GPX4 inhibitors and enhancing the efficacy of these inhibitors. This research investigates the regulatory mechanisms and properties of GPX4 in various tumor cell types, as well as its molecular structure and biological roles, hoping to propose more effective tumor-targeted therapy alternatives.